Enhanced tomato disease resistance primed by arbuscular mycorrhizal fungus - Song, Yuanyuan; Chen, Dongmei; Lu, Kai; Sun, Zhongxiang; Zeng, Rensen (Frontiers in Plant Science, 2015)
Roots of most terrestrial plants form symbiotic associations (mycorrhiza) with soil- borne arbuscular mycorrhizal fungi (AMF). Many studies show that mycorrhizal colonization enhances plant resistance against pathogenic fungi. However, the mechanism of mycorrhiza-induced disease resistance remains equivocal. In this study, we found that mycorrhizal inoculation with AMF Funneliformis mosseae significantly alleviated tomato (Solanum lycopersicum Mill.) early blight disease caused by Alternaria solani Sorauer. AMF pre-inoculation led to significant increases in activities of β-1,3-glucanase, chitinase, phenylalanine ammonia-lyase (PAL) and lipoxygenase (LOX) in tomato leaves upon pathogen inoculation. Mycorrhizal inoculation alone did not influence the transcripts of most genes tested. However, pathogen attack on AMF-inoculated plants provoked strong defense responses of three genes encoding pathogenesis-related (PR) proteins, PR1, PR2 and PR3, as well as defense-related genes LOX, AOC and PAL, in tomato leaves. The induction of defense responses in AMF pre-inoculated plants was much higher and more rapid than that in un-inoculated plants in present of pathogen infection. Three tomato genotypes: a Castlemart wild-type (WT) plant, a jasmonate (JA) biosynthesis mutant (spr2), and a prosystemin-overexpressing 35S::PS plant were used to examine the role of the JA signaling pathway in AMF-primed disease defense. Pathogen infection on mycorrhizal 35S::PS plants led to higher induction of defense-related genes and enzymes relative to WT plants. However, pathogen infection did not induce these genes and enzymes in mycorrhizal spr2 mutant plants. Bioassays showed that 35S::PS plants were more resistant and spr2 plants were more susceptible to early blight compared with WT plants. Our finding indicates that mycorrhizal colonization enhances tomato resistance to early blight by priming systemic defense response, and the JA signaling pathway is essential for mycorrhiza-primed disease resistance.